Discovery of the North Pole : Dr. Frederick A. Cook's own story of how he reached the North Pole April 21st, 1908, and the story of Commander Robert E. Peary's discovery April 6th, 1909 - Miller, J. Martin (James Martin), 1859-1939. ([Chicago? : s.n.], 1909)
Mode of access: Internet.